NMDAR Antibodies and New-Onset Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The frequency and significance of antibodies to NMDAR were determined in 19 adolescents and young women, aged 15 to 45 years, with unexplained new-onset epilepsies, seen between Jan 2005 and June 2007 at the University of Bonn, Germany; Univ of Pennsylvania, Philadelphia; and John Radcliffe Hospital, Oxford, UK.